On boundary conditions of the characteristic based split (CBS) algorithm for fluid dynamics - Nithiarasu, P. (International journal for numerical methods in engineering, 2002)
This paper discusses alternative procedures which can be used in the application of boundary conditions for the CBS algorithm. Attention is focused on the problem of application of prescribed velocity and traction conditions. The paper is illustrated with some incompressible flow problems. Although previously logical and correct boundary condition specifications were introduced, the procedures outlined in this paper simplify calculations and generally make it more accurate. Copyright © 2002 John Wiley & Sons, Ltd.